NiCuZn-based microwave gyromagnetic ferrite material with high dielectric constant and high saturation magnetization and preparation method thereof
By introducing Mn2+, Nb5+ and Ba0.6Sr0.4TiO3 composites into the spinel structure and adding Bi2O3, NiCuZn-based microwave rotary magnetite materials with high dielectric constant and high saturation magnetization are prepared, and high frequency band microwave devices are solved. The problem of insufficient material performance in the medium has achieved the possibility of miniaturization and high-frequency band applications.
Patent Information
- Application Number
- CN202410878948.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-frequency band microwave rotary magnetic devices lack rotary magnetic materials with high dielectric constant and high saturation magnetization, making it difficult to meet the needs of miniaturization and high-frequency band applications.
Using NiCuZn-based microwave spiral ferrites based on spinel structure, the dielectric constant and control are improved by introducing Mn2+, Nb5+ substitution and Ba0.6Sr0.4TiO3 composite and Bi2O3 as a sintering additive. Ferromagnetic resonance line width.
It has achieved both dielectric constants 22~31.6 and saturation magnetization 2905~3554Gs and ferromagnetic resonance line width 251~820Oe, significantly reducing the volume of microwave devices, and is suitable for miniaturized circulators and isolators in high-frequency bands.
Smart Images

Figure CN119170366A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of magnetic materials and their manufacturing, and relates to a high dielectric constant gyromagnetic ferrite, specifically a high dielectric constant and high saturation magnetization strength NiCuZn-based microwave gyromagnetic ferrite material and a preparation method thereof, which has both high dielectric constant (ε r ~22), high saturation magnetization (4πM s ~3554Gs) and narrow ferromagnetic resonance linewidth (△H~250Oe). Background Art
[0002] In microwave technology, microwave ferrite devices play an important role with their excellent performance and are widely used in electronic radar countermeasures, aerospace, industrial facilities, satellite communications and medical fields. As the technical basis of microwave ferrite components, microwave ferrite materials play an extremely important role in various microwave devices such as circulators and phase shifters, and complete microwave transmission intervals, direction selection, phase shift, polarization state detection, switching, regulation, frequency doubling, amplification and other functions in microwave control systems.
[0003] With the rapid development of microwave communication technology, microwave devices are required to be miniaturized and integrated in various advanced systems, and their circuit size needs to be smaller and smaller. Therefore, more stringent requirements are put forward for many performance parameters of microwave ferrite materials, such as dielectric constant, saturation magnetization intensity, ferromagnetic resonance line width, etc. Among them, dielectric constant is an important physical parameter that characterizes the dielectric properties or polarization properties of materials, and is one of the important performance indicators for designing microwave ferrite devices. Since the dielectric constant is inversely proportional to the size of microwave devices, improving the dielectric constant of materials plays a vital role in reducing the size of devices.
[0004] At present, there are many studies on high dielectric constant ferrite materials at home and abroad, mainly focusing on the yttrium iron garnet YIG system. CN111825441A discloses a high dielectric constant, high saturation magnetization strength garnet ferrite material, its preparation method and application. It is mainly through the introduction of Bi 3+ Replace Y 3+ , achieving a dielectric constant of 32-33, a ferromagnetic resonance line width of ≤50Oe, and a saturation magnetization intensity greater than 1850G. Patents such as CN115385680A, CN115385680A and CN116813321A introduce Bi 3+ ions, through Ca 2+ ,Zr 4+ ,Gd 3+Plasma further adjusts the dielectric constant and ferromagnetic resonance line width to achieve a dielectric constant of about 26 to 31, a ferromagnetic resonance line width of 20 to 50 Oe, and a saturation magnetization of 1200-1800 Gs. However, the saturation magnetization of ferrites in the YIG system is relatively low, and can only reach a maximum of about 1850 Gs, making it difficult to apply to higher frequency bands, such as the K band. Therefore, high-saturation gyromagnetic ferrite materials can only be achieved using spinel ferrites. However, there has been no report on the research on improving the dielectric constant of spinel gyromagnetic ferrite materials. Summary of the invention
[0005] In view of the above problems or shortcomings, in order to solve the application requirements of high-frequency microwave gyromagnetic devices for high dielectric constant and low line width of gyromagnetic materials, the present invention provides a high dielectric constant and high saturation magnetization strength NiCuZn-based microwave gyromagnetic ferrite material and a preparation method thereof. The material is based on a spinel structure, and its 4πM s The dielectric constant is between 2905 and 3554 Gs, the dielectric constant is between 22 and 31.6, and the ferromagnetic resonance linewidth is between 251 and 820 Oe, which can significantly reduce the size of the circulator and isolator, and thus reduce the mass and volume of the entire communication system, and has good application prospects.
[0006] A high dielectric constant and high saturation magnetization strength NiCuZn-based microwave gyromagnetic ferrite material based on spinel structure with the molecular formula (1-y)Ni 0.42-x / 3 Nb x / 3 Cu 0.18 Zn 0.4 Fe 1.98-x Mn x O4+y 0.6 Sr 0.4 TiO3+0.5wt%Bi2O3, 0.1≤x≤0.5, 5%≤y≤20%; its 4πMs is 2905~3554Gs, the dielectric constant is between 22~31.6, and the ferromagnetic resonance line width is 251~820Oe; it is prepared by solid phase reaction, and the sintering temperature is 975~1025℃.
[0007] The preparation method of the above-mentioned high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material comprises the following specific steps:
[0008] Step 1: Preparation of NiCuZn pre-sintered materials and Ba 0.6 Sr 0.4 TiO3 pre-burning material.
[0009] NiCuZn calcined material:
[0010] According to the molecular formula Ni 0.42-x / 3 Nb x / 3 Cu 0.18 Zn 0.4 Fe1.98-x Mn x O4 prepare analytically pure NiO, CuO, Fe2O3, ZnO, MnO and Nb2O5, 0.1≤x≤0.5; then ball-mill the prepared raw materials to mix them evenly, dry the obtained powder at 100-120°C after ball-milling, sieve it, and pre-sinter it at a heating rate of 3-5°C / min to 900-950°C, keep it warm for 4-6h, and cool it in the furnace to obtain NiCuZn pre-sintered material.
[0011] Ba 0.6 Sr 0.4 TiO3 pre-burning material:
[0012] Analytically pure SrCO3, BaCO3 and TiO2 are prepared in a molar ratio of SrCO3:BaCO3:TiO2=0.4:0.6:1, and then the prepared raw materials are ball-milled and mixed. After ball-milling, the obtained powder is dried at 100-120°C and sieved. After sieving, the temperature is raised to 1100-1200°C at a rate of 3-5°C / min for pre-calcination, and the temperature is kept for 4-6 hours, and the BaCO3 is cooled with the furnace to obtain BaCO3. 0.6 Sr 0.4 TiO3 pre-burning material.
[0013] Step 2: Pre-sinter the NiCuZn and Ba 0.6 Sr 0.4 TiO3 pre-sintered material, according to (1-y)NiCuZn+yBa 0.6 Sr 0.4 The weight ratio of TiO3+0.5wt%Bi2O3 is weighed and mixed, 5%≤y≤20%; then the powder is ball-milled again, dried at 100-120°C, and sieved for later use.
[0014] Step 3: Add the dried powder obtained in step 2 into the PVA solution as a binder, and granulate and press into shape.
[0015] Step 4: Put the product obtained in step 3 into a sintering furnace, heat it to 1000-1100°C after debinding, and sinter it completely. Finally, cool it to room temperature in the furnace to obtain a high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material.
[0016] Furthermore, in step 1, deionized water and ball milling medium are added according to the ingredients, deionized water and ball milling medium in a mass ratio of 1:1 to 3:4 to 6, and the ball milling is performed for 4 to 6 hours at a planetary ball mill speed of 300 rpm.
[0017] Furthermore, the sieve has a mesh size of 80 to 120.
[0018] Furthermore, in step 2, deionized water and ball milling medium are added according to the ingredients, deionized water and ball milling medium in a mass ratio of 1:1 to 3:4 to 6, and the ball milling is performed at a ball milling speed of 300 rpm for 6 to 12 hours.
[0019] Furthermore, the concentration of the PVA solution in step 3 is 5wt% to 11wt%.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention is based on spinel ferrite and introduces Mn 2+ , Nb 5+ Substitution and Ba 0.6 S r0.4 TiO3 composite effectively increases the dielectric constant of NiCuZn ferrite to 22-31.6, meeting the needs of miniaturization of microwave ferrite devices; it also controls Ba 0.6 S r0.4 The doping amount of TiO3 takes into account the comprehensive requirements of improving the dielectric constant and controlling the ferromagnetic resonance line width. Furthermore, by adding an appropriate amount of Bi2O3 as a sintering aid, the micromorphology of the ferrite material is optimized to improve the densification of the sintered sample, which is more conducive to reducing the ferromagnetic resonance line width and improving the dielectric constant.
[0022] In summary, the present invention provides a 4πM s The high dielectric constant and high saturation magnetization strength NiCuZn-based microwave gyromagnetic ferrite material has a dielectric constant of 2905-3554Gs, a dielectric constant of 22-31.6, and a ferromagnetic resonance linewidth of 251-820Oe. It makes it possible for gyromagnetic ferrite materials to have high dielectric constant, high saturation magnetization strength and low ferromagnetic resonance linewidth, providing a basis for the further miniaturization of microwave ferrite devices, and is very beneficial to the research and development and production of miniaturized circulators and isolators in the high-frequency band. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flow chart of the preparation process of the present invention.
[0024] Figure 2 This is the XRD test diagram of the embodiment.
[0025] Figure 3 4πM of the embodiment s Test picture.
[0026] Figure 4 This is a ferromagnetic resonance line width test diagram of the embodiment. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below with reference to specific embodiments and accompanying drawings.
[0028] A method for preparing a high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material (such as Figure 1 The specific steps are as follows:
[0029] Step 1: Preparation of NiCuZn pre-sintered materials and Ba 0.6 Sr 0.4 TiO3 pre-burning material;
[0030] NiCuZn calcined material:
[0031] According to the molecular formula Ni 0.42-x / 3 Nb x / 3 Cu 0.18 Zn 0.4 Fe 1.98-x Mn x O4 prepare analytically pure NiO, CuO, Fe2O3, ZnO, MnO and Nb2O5, 0.1≤x≤0.5; then add deionized water and ball milling medium in a mass ratio of 1:3:5, and ball mill for 6 hours at a planetary ball mill speed of 300rpm to mix the ingredients evenly; after ball milling, dry the obtained powder at 100°C and pass it through a 120-mesh sieve, sieve it and put it into an alumina crucible, heat it to 950°C at a heating rate of 2°C / min for pre-sintering, keep it warm for 4 hours, and cool it with the furnace to obtain NiCuZn pre-sintered material.
[0032] Ba 0.6 S r0.4 TiO3 pre-burning material:
[0033] Analytically pure SrCO3, BaCO3 and TiO2 were prepared in a molar ratio of SrCO3:BaCO3:TiO2=0.4:0.6:1, and then deionized water and ball milling medium were added in a mass ratio of 1:3:5, and the mixture was ball milled at a speed of 300 rpm for 6 hours to make the ingredients uniformly mixed; after ball milling, the obtained powder was dried at 100°C and passed through a 120-mesh sieve, sieved and placed in an alumina crucible, and pre-fired at a heating rate of 4°C / min to 1200°C, kept warm for 4 hours, and cooled with the furnace to obtain Ba 0.6 Sr 0.4 TiO3 pre-burning material.
[0034] Step 2: Pre-sinter the NiCuZn and Ba 0.6 S r0.4 TiO3 pre-sintered material, according to (1-y)NiCuZn+yBa 0.6 S r0.4The weight ratio of TiO3+0.5wt%Bi2O3 (5%≤y≤20%) is weighed and prepared; then deionized water and ball milling medium are added according to the weight ratio of 1:3:5, and ball milling is performed at a ball milling speed of 300rpm for 12h; after ball milling, the powder is dried at 100°C and passed through a 120-mesh sieve for later use.
[0035] Step 3: Add the dried powder obtained in step 2 into a PVA solution (concentration 11 wt%) as a binder, grind it evenly, granulate it and uniaxially dry press it into shape.
[0036] Step 4, placing the product obtained in step 3 into a sintering furnace, heating the temperature to 200°C at a heating rate of 2°C / min, keeping it warm for 2 hours to drain water, and then heating it to 550°C to drain the binder for 4 hours; then heating it to 1000-1100°C and keeping it warm for 6 hours, and finally cooling it to room temperature with the furnace to obtain a test sample of a high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material.
[0037] Table 1 shows the measured ε of different components (x, y are different) when sintered at 1000-1100℃ r Value (100MHz), 4πM s Value and △H value.
[0038] Table 1:
[0039]
[0040] Figure 2 This is the XRD test diagram of the embodiment with x=0.3 and y=5%. It can be seen from the figure that although a little impurity phase is generated in the composite ferrite, the main phase is still NiCuZn and Ba 0.6 Sr 0.4 TiO3. Figure 3 , Figure 4 The following are the test results of saturation magnetization and ferromagnetic resonance line width of high dielectric ferrite material prepared in Example x=0.3, y=5%, the dielectric constant of which is 21.8 at 100MHz, and the test is carried out under a magnetic field of saturation magnetization of 10000Oe, and the test is carried out using a waveguide resonant cavity method at a ferromagnetic resonance line width of 9.56GHz. As can be seen from the figure, the low line width ferrite material with high saturation magnetization and high dielectric constant prepared by the present invention has high saturation magnetization and dielectric constant characteristics, and at the same time has low ferromagnetic resonance line width, and can be applied to high-frequency microwave devices.
[0041] It can be seen from the above embodiments that the present invention is based on spinel ferrite and introduces Mn 2+ , Nb 5+ Substitution and addition of Ba 0.6 Sr0.4 TiO3 composite and trace doping of Bi2O3 during secondary ball milling can effectively improve the dielectric constant of NiCuZn ferrite and control the ferromagnetic resonance linewidth, meeting the needs of miniaturization of microwave ferrite devices; adding an appropriate amount of Bi2O3 as a sintering aid can optimize the densification degree of the sintered material, further helping to reduce the ferromagnetic resonance linewidth and increase the dielectric constant; the high dielectric constant and high saturation magnetization strength NiCuZn-based microwave gyromagnetic ferrite material finally prepared has 4πMs of 2905~3554Gs, a dielectric constant of 22~31.6, and a ferromagnetic resonance linewidth of 251~820Oe, which has high dielectric constant, high saturation magnetization strength and low ferromagnetic resonance linewidth, providing a basis for further miniaturization of microwave ferrite devices, and is very beneficial to the research and development and production of miniaturized circulators and isolators in the high frequency band.
Claims
1. A high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material, characterized in that: Based on the spinel structure, the molecular formula is (1-y)Ni 0.42-x / 3 Nb x / 3 Cu 0.18 Zn 0.4 Fe 1.98-x Mn x O4+y 0.6 Sr 0.4 TiO3+0.5wt%Bi2O3, 0.1≤x≤0.5, 5%≤y≤20%; its 4πMs is 2905~3554Gs, the dielectric constant is between 22~31.6, and the ferromagnetic resonance line width is 251~820Oe; it is prepared by solid phase reaction, and the sintering temperature is 975~1025℃.
2. The method for preparing the high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material according to claim 1, characterized in that: The specific steps are as follows: Step 1: Prepare NiCuZn pre-sintered material and Ba 0.6 Sr 0.4 TiO3 pre-burning material; NiCuZn calcined material: According to the molecular formula Ni 0.42-x / 3 Nb x / 3 Cu 0.18 Zn 0.4 Fe 1.98-x Mn x O4 prepares analytically pure NiO, CuO, Fe2O3, ZnO, MnO and Nb2O5, 0.1≤x≤0.5; then ball-mills the prepared raw materials to mix them evenly, and after ball-milling, dries the obtained powder at 100-120°C and sieves it, and after sieving, heats it to 900-950°C at a heating rate of 3-5°C / min for pre-sintering, keeps it warm for 4-6h, and cools it with the furnace to obtain NiCuZn pre-sintered material; Ba 0.6 Sr 0.4 TiO3 pre-burning material: Analytically pure SrCO3, BaCO3 and TiO2 are prepared in a molar ratio of SrCO3:BaCO3:TiO2=0.4:0.6:1, and then the prepared raw materials are ball-milled and mixed. After ball-milling, the obtained powder is dried at 100-120°C and sieved. After sieving, the temperature is raised to 1100-1200°C at a rate of 3-5°C / min for pre-calcination, and the temperature is kept for 4-6 hours, and the BaCO3 is cooled with the furnace to obtain BaCO3. 0.6 Sr 0.4 TiO3 pre-burning material; Step 2: Pre-sinter the NiCuZn and Ba 0.6 Sr 0.4 TiO3 pre-sintered material, according to (1-y)NiCuZn+yBa 0.6 Sr 0.4 The weight ratio of TiO3+0.5wt%Bi2O3 is weighed and mixed, 5%≤y≤20%; then the powder is ball-milled again, dried at 100-120°C, and sieved for later use; Step 3, adding the dried powder obtained in step 2 into the PVA solution as a binder, and granulating and pressing into shape; Step 4: Put the product obtained in step 3 into a sintering furnace, heat it to 1000-1100°C after debinding, and sinter it completely. Finally, cool it to room temperature in the furnace to obtain a high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material.
3. The method for preparing the high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material according to claim 2, characterized in that: In step 1, deionized water and ball milling medium are added according to the ingredients in a mass ratio of 1:1 to 3:4 to 6, and the ball milling is performed for 4 to 6 hours at a planetary ball mill speed of 300 rpm.
4. The method for preparing the high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material according to claim 2, characterized in that: The mesh size of the sieve is 80 to 120.
5. The method for preparing the high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material as claimed in claim 2, characterized in that: In step 2, deionized water and ball milling medium are added according to the ingredients, and the mass ratio of deionized water and ball milling medium is 1:1 to 3:4 to 6, and the ball milling is performed at a ball milling speed of 300 rpm for 6 to 12 hours.
6. The method for preparing the high dielectric constant and high saturation magnetization NiCuZn-based microwave gyromagnetic ferrite material according to claim 2, characterized in that: The concentration of the PVA solution in step 3 is 5wt% to 11wt%.
Citation Information
Patent Citations
Magneto-electricity composite material with huge dielectric constant and high magnetic conductivity and preparation method thereof
CN101747030A
Power type nickel-zinc ferrite material and preparation method thereof
CN106587977A
Preparation method of MnZn power ferrite with high mechanical strength, wide temperature range and wide frequency
CN114907106A
A broad band magneto-electric composite material and method for making same
CN1542875A
Composite sintered ceramic material
EP0351940A2
Cited By
LiZn gyromagnetic ferrite material as well as preparation method and application thereof
CN121651914A
